Obtenção, caracterização e estudo da degradação térmica e fotoquímica de blendas de poli(acetato de vinila) com lignina de bagaço de cana de açúcar - Silva, Marcela Fernandes (2009)
In this work, lignin was extracted from sugar cane bagasse with formic acid and then the acetone soluble formic lignin fraction (FLBC) was obtained in a soxlhet system. This lignin sample was used for blends preparation with poly(vinylacetate) (PVAc). They were prepared by casting from acetone solutions with the FLBC/PVAc compositions of 5/95, 10/90 and 15/85. The films were irradiated with UV light of a Hg lamp whose fluence was 48 mJ/m2s (measured at the film surface). These samples were analyzed through DSC, TGA, FTIR, MEV, AFM and contact angle measurements. The FLBC/PVAc films showed an increasing thermal stability when irradiated while PVAc films showed the opposite behavior. Theoretical FTIR, DSC and TGA curves for the blends were also simulated by adding the pure components curves in the corresponding proportions. These results suggest specific intermolecular interactions between the polar functional groups of the polymer chains. SEM micrographies revealed that irradiation causes polymer photodegradation of PVAc film surface which is minimized in the FLBC/PVAc films. AFM images showed that the film surface becomes more irregular when lignin is incorporated to PVAc and also when they are irradiated. From contact angle data it can be inferred that FLBC/PVAc films surface is more hydrophobic than PVAc film surface. Contact angles of the irradiated films were lower than the corresponding non-irradiated, indicating surface irregularity and /or hydrophylicity increase due to irradiation. The kinetics analyses of the thermal degradation reaction of the samples revealed lower apparent activation energy for the FLBC/PVAc than for the PVAc although this reaction occurs at higher temperature in the FLBC/PVAc blends. A 2 5-2 fractional factorial design was applied to TGA data and the most important result observed was that heating rate is a significant factor for the Tmax and T90 responses.